Sustainable development and proximity city. The environmental role of new public spaces - Bocca, Antonio (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Biodiversity, urban regeneration and the climate crisis are inseparable issues and must be addressed simultaneously. The article addresses the potential synergy of the 15-minute city approach to the environmental role of new public spaces. There is a need for a multi-scalar and cross-sectoral approach to open space design that considers environmental resources and components as levers for urban regeneration and socio-economic development. Rethinking the city is part of rethinking the relationship between density, land consumption and sustainability, in which interventions transcend public-private space dichotomies through strategic spatial planning. Proximity can give shape, direction, and meaning to the development of settlement systems. Networks and relationships between spaces and land values must consider environmental dominants as part of spatial design. In this sense, new ecological public spaces can contribute to climate adaptation and increased urban well-being. The paper consists of two main sections: the first focuses on global challenges and the planning of resilient cities; the second deals with theoretical and application aspects of the concept of proximity about ecological transition.